Quadriparesis Following Intrinsic Traumatic Esophageal Perforation: Report of a Rare Case - Anchal Awasthi; Sunil Kumar Singh; Ahemadullah Shaikh; Saurabh Kumar Verma; Shuchi Singh (Indian Journal of Neurosurgery)
An elderly diabetic gentleman developed epidural abscess several days after traumatic esophageal perforation secondary to flexion-extension injury of the cervical spine in a road traffic accident. The patient underwent high-resolution ultrasonography of the neck along with noncontrast computed tomography and magnetic resonance imaging of the cervical spine, which showed collection in soft tissue of the neck region along with epidural abscesses and osteophytes at multiple levels. However, due to the rarity of cervical esophageal perforation due to vertebral osteophytes, esophageal perforation was missed and was only diagnosed during the second admission of the patient, about 1 month later, when he presented with progressive quadriparesis. We present an extremely rare case of cervical esophageal perforation due to a flexion-extension injury.